The relationship between social media addiction, insomnia, and depression in adolescents - Ciftci, Necmettin; Sarman, Abdullah; Coban, Mahmut (Routledge Journals, Taylor & Francis Ltd, 2025)
This study aims to investigate the relationship between social media addiction, insomnia, and depression in adolescents. This correlational-cross-sectional-descriptive study involved 780 adolescents (mean age: 15.11 +/- 1.20; 50.5% female) from high schools in a city center in Eastern Turkey. Data were gathered using a personal information form and validated scales, including the Bergen Social Media Addiction Scale, Bergen Insomnia Scale, and 6-item Kutcher Depression Scale. Data analysis was performed using SPSS 25.0, AMOS V 24.0, and G*Power 3.1 statistical package programs. It was determined that the mean score of adolescents' social media addiction was 15.81 +/- 5.50, the mean score of insomnia was 16.98 +/- 10.84 and the mean score of depression was 7.30 +/- 4.47. A significant positive relationship was observed between social media addiction and both insomnia and depression. Additionally, insomnia and depression were significantly correlated. Social media usage time was positively associated with higher levels of social media addiction, insomnia, and depression. Depression was found to mediate the relationship between social media addiction and insomnia. Pediatric and school health nurses are encouraged to assess adolescents' social media usage habits, including time spent online, and develop monitoring and intervention programs. These programs can provide immediate support to address social media-related psychological and behavioral issues effectively.
Keywords: Adolescent; depression; insomnia; nursing; social media addiction